Hydatid disease presenting as an intrascrotal mass in a child - Kızılcan, Fatih; Tanyel, F. Cahit; Büyükpamukçu, Nebil; Hiçsönmez, Akgün (The Turkish Journal of Pediatrics, 1991)
A thirteen-year-old boy with the preliminary diagnosis of hydrocele of the cord who underwent surgery is presented. Ultimate diagnosis of hydatid disease was established by surgical exploration and histopathologic examination of the specimen. Although it is a rare occurrence, hydatid disease should be considered as a diagnostic possibility in endemic areas.